The Development of Learning Resources in Schools for Enhancing Critical Thinking Skills Through Media Literacy Processes of Elementary School Students in Schools Under Chiang Mai Provincial Primary Education Service Area Office - Chuenchom, Sutthinan (Journal of Information Science Research and Practice, 2025)
Purpose: 1) To study conditions, problems, and use of learning resources in schools to develop critical thinking skills of elementary school students in schools under the Office of the Primary Educational Service Area, Chiang Mai Province. 2) To study guidelines for developing learning resources in schools to enhance critical thinking skills through the media literacy process of elementary school students in schools under the Office of the Primary Educational Service Area, Chiang Mai Province. Methodology: This research employs a mixed-methods approach, combining quantitative and qualitative data. The quantitative sample consists of school administrators, teachers instructing in grades 4-6, as well as librarians or teachers responsible for the school’s library, totaling 330 individuals. The quantitative research instrument is a questionnaire, while the qualitative research involves focus group discussions with school representatives, including school administrators, teachers, and librarians, totaling 30 individuals. Findings: Guidelines for developing learning resources in schools to enhance the critical thinking skills of elementary students through media literacy processes include the development of physical environments, preparation of learning resources, organization of services and learning promotion activities, and community participation. Applications of this study: As guidelines for developing learning resources in schools to enhance the critical thinking skills of elementary school students through media literacy processes, the government, the Ministry of Education, school administrators, teachers, librarians, educational personnel, and parents, have recognized the importance of critical thinking skills and media literacy. They value learning resources both inside and outside the classroom and can use them as a guideline for developing learning resources to enhance students’ critical thinking skills.